Obiekt rowkowy z Inowrocławia-Mątew, stan. I - Cofta-Broniewska, Aleksandra (Acta Universitatis Lodziensis. Folia Archaeologica, 1992)
The results of the researches on the beliefs of prehistoric communities in Kuyavia indicate that the centres of religious cult from the close of antiquity, numerous in that region, are linked with the earlier Lusatian tradition. This is confirmed by the excavations of Inowrocław-Mątwy, site 1. Two features that should be connected with cult practices have been recorded there. The sanctuary consists of a ditch which enclosed a sacral space with a temple of post construction, built above ground, as a central feature. It can be regarded as a simpler form of the later, more developed „Przeworsk" sanctuaries of Kuyavia with a very differentiated inner built-up. During the Lusatian culture, these features were located near water and away from settlement concentrations. The accumulation of pottery and of remains of sacrificial animal burials in the form of uncremated bones or cremated remains ia also a characteristic attribute. Thus in the light of archaeological findings the Lusatian people seem to have worshipped their deities not only by depositing numerous votive offerings in various water regions but also through other ritual practices performed within appropriately built-up sacral centres set apart for this purpose.